Ambulance-based assessment of NIH Stroke Scale with telemedicine: A feasibility pilot study. (May 2017) - Barrett, Kevin M; Pizzi, Michael A; Kesari, Vivek; TerKonda, Sarvam P; Mauricio, Elizabeth A; Silvers, Scott M; Habash, Ranya; Brown, Benjamin L; Tawk, Rabih G; Meschia, James F; Wharen, Robert; Freeman, William D
Background: Ischemic stroke is a time-sensitive disease, with improved outcomes associated with decreased time from onset to treatment. It was hypothesised that ambulance-based assessment of the National Institutes of Health Stroke Scale (NIHSS) using a Health Insurance Portability and Accountability Act (HIPAA)–compliant mobile platform immediately prior to arrival is feasible. Methods: This is a proof-of-concept feasibility pilot study in two phases. The first phase consisted of an ambulance-equipped HIPAA-compliant video platform for remote NIHSS assessment of a simulated stroke patient. The second phase consisted of remote NIHSS assessment by a hospital-based neurologist of acute stroke patients en route to our facility. Five ambulances were equipped with a 4G/LTE-enabled tablet preloaded with a secure HIPAA-compliant telemedicine application. Secondary outcomes assessed satisfaction of staff with the remote platform. Results: Phase one was successful in the assessment of three out of three simulated patients. Phase two was successful in the assessment of 10 out of 11 (91%) cases. One video attempt was unsuccessful because local LTE was turned off on the device. The video signal was dropped transiently due to weather, which delayed NIHSS assessment in one case. Average NIHSS assessment time was 7.6 minutes (range 3–9.8 minutes). Neurologists rated 83% of encounters as 'satisfied' to 'very satisfied', and the emergency medical service (EMS) rated 90% of encounters as 'satisfied' to 'very satisfied'. The one failed video attempt was associated with 'poor' EMS satisfaction. Conclusion: This proof-of-concept pilot demonstrates that remote ambulance-based NIHSS assessment is feasible. This model could reduce door-to-needle times by conducting prehospital data collection.